AB0590 Prolactin Levels are Associated with a Pro-Inflammatory Body Mass Distribution Among Systemic Lupus Erythematosus Female Patients. (9th June 2015) - Ugarte-Gil, M.F.; Gamboa-Cardenas, R.V.; Zevallos, F.; Cucho-Venegas, J.M.; Perich-Campos, R.A.; Alfaro-Lozano, J.L.; Medina, M.; Rodriguez-Bellido, Z.; Alarcόn, G.S.; Pastor-Asurza, C.A.
Abstract : Background: Chronic inflammatory conditions are associated with a decrease of bone mineral density (BMD) and lean mass (in particular low appendicular lean mass) and an increase of fat mass (in particular areas considered more pro-atherogenic, like trunk fat mass or trunk-to-leg fat ratio). As prolactin (PRL) has a pro-inflammatory function in systemic lupus erythematosus (SLE) and it is associated with disease activity and damage, it would be expected that PRL could be associated with a decrease of BMD and lean mass and an increase of fat mass. Objectives: To determine whether PRL levels are associated with a pro-inflammatory body mass distribution in female SLE patients. Methods: This cross-sectional study was conducted in consecutive SLE female patients seen in our Rheumatology Department from 2012 to 2014. For the purpose of this study, baseline visits were included. Overweight patients (more than 115 kg), those with metallic implants or pregnant were excluded for this analysis. Disease activity was ascertained using the SLEDAI and disease damage with the SLICC/ACR damage index (SDI). PRL was measured in ng/ml. Body mass distribution was measured by DXA and it was divided into sub-total (whole body without the head) BMD, sub-total bone mineral content (BMC), lean mass index (appendicular lean mass/height 2, LMI), sub-total, trunk and leg fat percentages and trunk-to-leg fat ratio. A pro-inflammatory body mass distribution is defined as a decrease of BMD, BMC and LMI and an increase of fat mass, in particular trunk fat mass and trunk-to-leg fat mass ratio. The association between PRL levels and body mass distribution components was evaluated by univariable and multivariable linear regression models, the last one adjusted for age, disease duration, SLEDAI, SDI, use of prednisone, antimalarials and immunosuppressive drugs. Results: One hundred and fifty-five patients were evaluated; their mean (SD) age was 42.7 (13.4) years; nearly all patients were Mestizo. Patients included in this study had a lower body mass index than the rest of the cohort. Age, disease duration, SLEDAI and SDI were similar than the rest of the cohort. Disease duration was 7.3 (6.6) years. The SLEDAI was 5.5 (4.1) and the SDI 0.8 (1.3). PRL levels were 18.8 (14.3) ng/ml. BMD was 0.9 (0.1) g/cm 2, BMC was 1.4 (0.3) kg, LMI 6.1 (1.1) kg/m 2, percentage of subtotal fat 36.7 (6.7), trunk fat 34.3 (7.6), leg fat 37.9 (6.7), trunk-to-leg fat ratio 1.5 (0.6). Multivariable analysis is depicted in Table 01 . Conclusions: Higher PRL levels are associated with a pro-inflammatory body mass distribution in SLE patients. Disclosure of Interest: None declared